2022
DOI: 10.1186/s12888-022-03903-5
|View full text |Cite
|
Sign up to set email alerts
|

PTSD is not the emblematic disorder of the COVID-19 pandemic; adjustment disorder is

Abstract: Background Posttraumatic stress disorder (PTSD) has been hailed by some as the emblematic mental disorder of the COVID-19 pandemic, assuming that PTSD’s life-threat criterion was met de facto. More plausible outcomes like adjustment disorder (AD) have been overlooked. Methods An online cross-sectional survey was launched in the initial stage of the pandemic using a convenience sample of 5 913 adults to compare the prevalence of COVID-related probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Moreover, a previous study suggested that frequent exposure to information regarding the COVID-19 outbreak, fear of contagion, and hypochondriasis symptoms would, in turn, increase individuals' susceptibility to maladjustment to stressful situations [24]. It should be noted that several profiles of responses to the pandemic have been found in AD patients [25], and thus different explanations might apply to different AD sub-groups. Unfortunately, we could not fully address this possibility here because of the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study suggested that frequent exposure to information regarding the COVID-19 outbreak, fear of contagion, and hypochondriasis symptoms would, in turn, increase individuals' susceptibility to maladjustment to stressful situations [24]. It should be noted that several profiles of responses to the pandemic have been found in AD patients [25], and thus different explanations might apply to different AD sub-groups. Unfortunately, we could not fully address this possibility here because of the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is debate regarding if the COVID-19 pandemic constitutes a life-threatening Criterion A stressor according to the DSM-5 PTSD diagnostic criteria (Bridgland et al, 2021; Brunet et al, 2022; Van Overmeire, 2020). Perhaps rather than focusing on PTSD alone, other stressor-related disorders, such as adjustment disorder, may provide a better framework for understanding the mental health impact of the pandemic (Brunet et al, 2022). While the IES-R is validated to screen for PTSD, it is not a diagnostic tool and can only suggest likely clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the new, preliminary evidence on adjustment disorder symptoms could broaden the scope of psychiatric assessment amid different forms of disasters. Adjustment disorder could be one of the more prevalent but overlooked mental health consequences of COVID‐19 among other large‐scale disasters (Brunet et al, 2022). Previous studies in European countries found that COVID‐19‐induced stressors, alongside other work‐related, financial, and family stressors, low socioeconomic status, and existing health problems, were predictive of adjustment disorder symptoms (Dragan et al, 2021; Lotzin et al, 2021; Rossi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%